Assessment Higher Education Perspective by Tenure of Lecturer Thesis Student Undergraduate: Elista - Jefri Marzal; Edi Elisa; Pradita Eko Prasetyo Utomo; Dwi Agus Kurniawan; Muhammad Iqbal (Jurnal Pendidikan dan Pengajaran, 2022)
The problem that often occurs during lectures is the mismatch of time from the supervisor's response which becomes a very difficult challenge for students in doing their final project/thesis. The purpose of this study was to analyze the supervisor's response time in conducting thesis guidance using Elista which was differentiated based on years of service. This research is a mixed method research with explanatory design, where quantitative data is strengthened by qualitative data. The population in this study were lecturers with a sample selection technique using purposive sampling technique with the sample criteria being lecturers who had become student thesis supervisors so that a sample of 1270 lecturers was obtained which was grouped into 4 work intervals, namely 1-10 years, 11-20 years. years, 21-30 years, and 31-40 years. Data collection in this study was obtained through the Elista database regarding the supervisor's response time and through interviews with lecturers from each working period. Analysis of quantitative data using descriptive analysis and qualitative data using analysis of Miles and Huberman. The results showed that lecturers with 1-10 years of service and 11-20 years had better guidance response times than lecturers with longer tenures because lecturers with 1-10 years of service were more productive in using technology and strongly supported the fast response of supervisors. The implication of this research is that to speed up the travel time of student graduation, a good response from the supervisor is needed, where this response can also be distinguished by the tenure of the lecturer.